DEM-based study of hydraulic fracturing mechanism under high internal water pressure - Jiang, Tao; Wu, Zhaofeng; Shan, Shengbiao; Zhong, Qikai; Lu, Qingbi; Yang, Pengliang (Frontiers in Environmental Science, 2023)
To solve the problem of fracturing due to high water pressure when pumping in the diversion tunnel, the mechanism of hydraulic fracturing (HF) in the tunnel under high internal water pressure is studied. A numerical model of HF considering water-rock interaction is established using the PFC 2D discrete element simulation software. The HF mechanism of surrounding rock under high internal water pressure is studied, and the development process of hydraulic cracks is obtained. The influence of surrounding rock parameters on fracturing is analyzed and the law between principal stress and crack development is investigated. The high-pressure water injection test under different tunnel diameters is also carried out. Numerical test research shows that under the action of high internal water pressure, the surrounding rock at the cavity wall splits first, and the water entering the crack generates water pressure on the crack sidewall, which in turn generates tensile stress at the crack tip and further causes the crack expansion. The crack length is exponentially related to the internal water pressure. The high internal water pressure decays gradually with the crack extension distance and stabilizes when the crack extension reaches a certain length because the water pressure is less than the tensile strength of the surrounding rock. The fracturing results indicate that the process of HF damage is tensile types, and the increase of cohesion plays a suppressive role in crack opening, while the internal friction angle has little effect on the HF effect. The influence of principal stress on the HF result shows that the direction of HF is along the direction of major principal stress. The major principal stress promotes the cracking, while the minor principal stress inhibits the crack growth. By simulating the water injection test for different hole diameters of the diversion tunnel, it is found that the fracturing distance of the surrounding rock increases approximately linearly with the increase of the hole diameter. The test results can provide a basis for the design and construction of high-pressure tunnels such as pumped storage power plants.